Pengaruh Inovasi Produk terhadap Keunggulan Bersaing: Studi Kasus Toko Sinar Abadi Mutiara, Kota Mataram - Salsabila Aurellia; Eka Yuliana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Indonesia is the fifth largest pearl exporting country in the world. One of the locations in Indonesia that produces pearls is the island of Lombok, which is already famous for the beauty of its pearls that attract the interest of the global export market. The pearl handicraft industry in Lombok, such as Toko Sinar Abadi Mutiara, is faced with a problem in the form of increased competition reinforced by the large number of physical and online stores selling pearl handicrafts with the presence of the MotoGP circuit in Mandalika. Despite the increased competition, the store has not utilized the e-commerce platform and has not fully adapted in terms of product innovation to changing consumer preferences, characterized by the release of new products only at the end of the year. The purpose of this study is to analyze how much influence product innovation simultaneously and the dimensions of product innovation on competitive advantage at Toko Sinar Abadi Mutiara. The quantitative approach was used in this study with questionnaires distributed through Google Form as a primary data source and analyzed using IBM SPSS 23 software. The results of this study indicate that product innovation simultaneously and the 4 dimensions of product innovation have a positive influence on competitive advantage at Toko Sinar Abadi Mutiara, Mataram City.